Measuring and Ranking Value Drivers - Mehari Mekonnen Akalu (Tinbergen Institute, 2002)
Analysis of the strength of value drivers is crucial to understand their influence in the process of free cash flow generation. The paper addresses the issue of value driver measurement and ranking. The research reveals that, value drivers have similar pattern across industries. Furthermore, it is found that the effect of operating cost and interest expenses, on free cash flow, is much more important than sales (revenue).
Keywords: 330; Free cash flow; Value Management Techniques; Shareholder Value Analysis; Value drivers; Performance measurements; Sensitivity analysis